Breast carcinoma metastasis to meningioma in the thoracic spine: A case report and review of the literature. (March 2015) - Okada, Eijiro; Nakamura, Masaya; Koshida, Yoshitomo; Mukai, Kiyoshi; Toyama, Yoshiaki; Matsumoto, Morio
Abstract : Context: Systemic metastasis to a primary tumor of the central nervous system is uncommon. Breast carcinomas metastasizing to a possibly preexisting meningioma in the spine are reported very rarely. Study design: Case report. Findings: A 69-year-old female was referred to us with progressive gait disturbance. She had undergone a total mastectomy for carcinoma of the right breast 11 years previously. A magnetic resonance imaging of the thoracic spine showed an intra- and extradural spinal cord tumor. The patient underwent resection of the tumor via laminectomy from T2 to T4. After the operation, the patient's neurological status improved significantly, and she was able to walk without assistance. Histological examination showed the tumor to be a fibrous-type meningioma within a metastatic breast cancer tumor. The patient underwent 40 Gy radiation treatment for local control of the tumor. However, the tumor recurred locally 7 months after the surgery. The patient died of carcinomatous pleurisy 13 months after the surgery. Conclusion: This case illustrates that a primary meningioma in the thoracic spine can be a recipient of breast cancer metastasis, which may alter the treatment strategy.